2015
DOI: 10.2169/internalmedicine.54.3800
|View full text |Cite
|
Sign up to set email alerts
|

Portosystemic Encephalopathy without Liver Cirrhosis Masquerading as Depression

Abstract: A 69-year-old woman was hospitalized due to progressive lethargy with hyperammonemia. Five months before the current admission, she was diagnosed with depression based on her low level of daily physical activity and thus began taking antidepressants. Abdominal computed tomography revealed a portosystemic shunt running between the left renal vein and inferior mesenteric vein. Balloon-occluded retrograde transvenous obliteration of the shunt vessel was performed, and the patient showed a remarkable clinical impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
1
6
0
Order By: Relevance
“… 43 , 44 It seems, however, that embolization of portosystemic shunts may be more effective in patients without underlying cirrhosis. 38 , 39 , 45 …”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 It seems, however, that embolization of portosystemic shunts may be more effective in patients without underlying cirrhosis. 38 , 39 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…One study in Japan reported 47 cases of hepatic encephalopathy in the absence of underlying liver disease in the year 2000 [9]. Another study found that an additional 24 cases have been reported worldwide through 2015 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Time to occlusion is also very short with use of Amplatzer device as compared to coils alone allowing for thorough evaluation of the shunt occlusion during the procedure. It is also superior to embolization with ethanol because you do not risk hemolysis and pulmonary edema [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Encephalopathy from IPSSwoC intermittently occurs in the elderly, probably because of the irregular susceptibility of the brain to ammonia by aging. 6,7 To understand the correlation between blood ammonia levels and the PSE, we extracted Japanese congenital or idiopathic PSS without cirrhosis cases from the National Center for Biotechnology Information literature search sites 3,820 and estimated grades of PSE based on the symptoms described in them according to the guideline 21 (Table 2). There was a moderate correlation between blood ammonia levels and the estimated grades of PSE of PSS without cirrhosis (Figure 2, r 2 = 0.495).…”
Section: Discussionmentioning
confidence: 99%